Creating Brand India: Strategies, Issues, and Challenges - Alok Chakrawal; Pratibha Goyal (Technology Innovation Management Review, 2016)
Just like a product, person, or institution, a country also has an impression in the minds of people. A brand distinguishes the product of one seller from those of the others. With the Indian Prime Minister's recent call to "Make in India", brand building is receiving more attention and momentum in the country. India is the largest democratic country with the highest GDP, and it is becoming a favourable destination for the global investment giants. But, despite various strengths and successes in image building, the country faces challenges in creating a sustainable, conducive environment for making India a production hub of the world. Bureaucracy, corruption, delay in clearance of business proposals, ethical standards and work culture, tax reforms, political interventions, socio-economic barriers, regionalism, etc. are some of the challenges that must be coped with. This article examines these various issues and challenges that must be overcome in creating Brand India.
Keywords: Brand India; challenges; economic growth; entrepreneurship; government initiatives; innovation; Make in India